Facility layout Design and its impact on the Healthcare Service Quality in Teaching Hospital and Pediatric Teaching Hospital in Sulaymaniyah city - Othman Kareem Mahmood; Jamal Ahmed Hama Kareem; Wirya Najm Rashid; Daroon Faridun Abdulla (International Review of Management and Marketing, 2017)
This paper explores the relationship between the physical facility layout of the Sulaymaniyah Pediatric Teaching Hospital (SPTH) and Sulaymaniyah Teaching Hospital (STH) and the quality of healthcare service dimensions using the correlation coefficient and linear regression model. It is concluded that there is a statistically significant correlation between facility layout design of the hospitals and the quality of healthcare services offered, in addition to the causal relationship, as a regression, between the facility layout of the public hospitals and the quality of the healthcare service they offer. The recommendation for the two hospitals suggested is improving the quality of healthcare service through redesigning the physical facility layout design.